2016
DOI: 10.18632/oncotarget.14105
|View full text |Cite
|
Sign up to set email alerts
|

Papanicolaou Society of Cytopathology new guidelines have a greater ability of risk stratification for pancreatic endoscopic ultrasound-guided fine-needle aspiration specimens

Abstract: The Papanicolaou Society of Cytopathology has recently proposed a standardized terminology and nomenclature guidelines for pancreatic cytology. However the risk of malignancy associated with the new guidelines has been scarcely studied. In this study, a series of pancreatic cytology cases obtained by endoscopic ultrasound-guided fine-needle aspiration from 294 Chinese patients were retrospectively re-categorized into six categories according the new guidelines. The risks of malignancy were 18.1% for “negative,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…One of the most egregious results in the study was the high rate of inadequacy in specimens. The nondiagnostic rate of 21.2% is higher than rates reported by other authors, ranging from 3.8%‐11.7% 9‐12 . The explanation is multifactorial.…”
Section: Discussionmentioning
confidence: 57%
“…One of the most egregious results in the study was the high rate of inadequacy in specimens. The nondiagnostic rate of 21.2% is higher than rates reported by other authors, ranging from 3.8%‐11.7% 9‐12 . The explanation is multifactorial.…”
Section: Discussionmentioning
confidence: 57%
“…Studies by Chen et al, 12 Hoda et al 13 and Sung et al 14 have demonstrated the reliability of the PSC categories in malignancy risk stratification.…”
Section: Discussionmentioning
confidence: 98%
“…The incorporation of the PB System, as described in the present review, has also assisted its improvement. The use of ROSE has also shown to increase diagnostic yield, decreasing the number of nondiagnostic samples, time of the procedure, and complications . More recently, next‐generation “core‐type” needles have been used, producing larger tissue fragments.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The distribution of the cases using the PB system from studies looking at pancreatic FNA specimens places most cases in the negative for malignancy and malignant categories [2][3][4][5][6][7][8][9] (Table 1). In fact, one of the clear benefits of implementing the PB System is the ability to decrease the number of indeterminate interpretations (eg, atypical and nondiagnostic).…”
Section: Experience With the Use Of The Pb System Worldwidementioning
confidence: 99%
See 1 more Smart Citation